The Using of Media Games to Improve SMCP (Standard Marine Communication Phrases) Vocabulary in Maritime English - Tekat Sukomardojo (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: Shipping is the world's largest trade and also one of the most dangerous. Safety of life at sea, the environment at sea, and 80% of world trade depend on professional and competent seafarers. Ziarati (2006) identified that poor communication as one of the most significant factors in accidents at sea and ports. SMCP is a collection of words or phrases in English which is supported by the international community means of communication at sea then developed and adapted to IMO (International Maritime Organization) standards. SMCP aims to explain external communication phrases such as communication between ships, between ships and land parties such as ports. The main goal is to reduce language problems in communicating at sea and also to avoid misunderstandings that can lead to accidents. So, it is possible to learn vocabulary in SMCP to achieve maximum results if it is done in a pleasant atmosphere. Design/methodology/approach: This study uses a quantitative approach using a quasi-experimental method. Findings: In this study, the result in question was the use of games to support the learning of maritime English SMCP vocabulary. Research limitations/implications: The population in this study was the cadets of the diploma program majoring in Nautica in the second semester of The Surabaya Shipping Polytechnic (2015-2016) academic year, amounting to 110 people. The sample of this study was 20 cadets in class C. Paper type: A case study